Pengaruh Iklan, Harga Dan Brand Image Produk Kecantikan Merek Scarlett Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Pengguna Produk Scarlett Mahasiswa Universitas Islam Malang) - Hikmatun Nafiah Ali; Rois Arifin; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of advertising, price and brand image on purchasing decisions for Scarlett brand beauty products. The location of this research was carried out on students of the Islamic University of Malang who became consumers of Scarlett brand beauty products. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to students of the Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Ferdinand formula and the results obtained were 75 respondents. Data were analyzed using multiple linear regression and determination test. Based on the results of data analysis, the results of the F test show that Advertising, Price and Brand Image have a significant and positive effect on purchasing decisions for the Scarlett brand of beauty products. Furthermore, the results of the t test show that advertising, price and brand image partially have a significant and positive effect on purchasing decisions for Scarlett brand beauty products. The results of the determination test show that the percentage is 56.7% where purchasing decisions can be influenced by Advertising, Price and Brand Image. Keywords: Purchase Decision, Advertising, Price and Brand Image